Effect of intervertebral foramen area and width on postoperative pain relief in patients with cervical spondylotic radiculopathy - Shuang Liu; Peng Pu; Qing Xiang; Jie Chen; Guangye Wang; Xiangling Pu (BMC Surgery)
Abstract Objective This study aims to investigate the relationship between preoperative cervical intervertebral foramen width and area and the persistence of postoperative pain in patients diagnosed with cervical spondylotic radiculopathy (CSR). Methods Patients were divided into two groups, based on their pain relief at the 6-month postoperative follow-up: the pain relief group and the persistent pain group. We compared various parameters, including age, sex, body mass index (BMI), duration of symptoms, preoperative Japanese Orthopedic Association (JOA) score, Neck Disability Index (NDI) score, postoperative ratio of disc space distraction, preoperative width of the intervertebral foramen (WIVF), and area of the intervertebral foramen (AIVF) between the two groups. Binomial logistic regression analysis was conducted to identify the factors affecting pain relief. Results Significant differences were observed in preoperative WIVF, AIVF, duration of symptoms, preoperative NDI scores, and the ratio of disc space distraction between the two groups (all P < 0.05). Regression models indicated that symptom duration, preoperative NDI score and ratio of disc space distraction were negatively associated with pain relief, whereas preoperative WIVF and AIVF were positively associated with pain relief. Conclusion Preoperative WIVF and AIVF may be linked to persistent postoperative pain in patients with CSR.